Progressive transformations of written socio-affective competence in early childhood education students - Dulcic, Francisco Jose Leria; Orellana, Patricia Ester Sasso; Pena, Roxana Nora Acosta; Morales, Mirna Pizarro; Avila, Monica Yudy Avila (My University, 2024)
Early childhood educator's linguistic ability has not often been a subject of study, considering the specificity of a language evolutionarily adapted to infants, but that involves technicalities and a particular style of evocation. The purpose of the present study is to describe the progressive use of written socio-affective language of early childhood education students, belonging to various educational levels. A quantitative approach and a cross-sectional and descriptive design were selected to evaluate 286 participants that addressed the affective connotation of lexical units according to 8 psycholinguistic properties: Valence, Excitability, Familiarity, Imaginability, Origin, Concreteness, Subjective significance, and Manipulability. The findings show a significant differentiation between most of the properties, in addition to differential behaviors associated with the educational levels. The findings regarding the characterization of early childhood's socio-affective competence are discussed, and conclusions briefly are made about its role in higher education's initial training processes.
Keywords: communicative competence; teaching profession; affectivity and sentiment; written language